In vivo Screen Identifies Zdhhc2 as a Critical Regulator of Germinal Center B Cell Differentiation - Zhao, Rongqing; Zhang, Huihui; Zhang, Yan; Li, Dan; Huang, Chuanxin; Li, Fubin (Frontiers in Immunology, 2020)
Germinal center (GC) B cell differentiation is critical for the production of affinity-matured pathogen-specific antibodies, the dysregulation of which may lead to humoral immunodeficiency or autoimmunity. The development of in vivo screening system for factors regulating GC B cell differentiation has been a challenge. Here we describe a small-scale in vivo screening system with NP-specific B1-8hi cells and a retroviral shRNA library targeting 78 candidate genes to search for B cell-intrinsic factors that specifically regulate GC B cell differentiation. Zdhhc2, a gene encoding palmitoyltransferase ZDHHC2 and highly expressed in GC B cells, is identified as a strong positive regulator of GC B cell differentiation. B1-8hi cells transduced with Zdhhc2-shRNA are severely compromised in differentiating into GC B cells. Further analysis of in vitro differentiated B cells transduced with Zdhhc2-shRNA shows that Zdhhc2 is critical for the proliferation and survival of B cells stimulated by CD40L, BAFF, and IL-21, and consequently impacts on their differentiation into GC B cells and post-GC B cells. These studies not only identify Zdhhc2 as a novel regulator of GC B cell differentiation but also represent a proof of concept of in vivo screen for regulators of GC B cell differentiation.